2010
DOI: 10.1111/j.1530-0277.2010.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Serum, Liver, and Brain Cytokine Induction, Thiamine Levels, and Hepatopathology in Rats Exposed to a 4‐Day Alcohol Binge Protocol

Abstract: Background In rodent and human studies, ethanol (EtOH) exposure is associated with elevated brain levels of the magnetic resonance spectroscopy (MRS) signal representing choline-containing compounds (Cho). One interpretation of elevated brain Cho is that it is a marker of neuroinflammation, and some evidence suggests that EtOH exposure promotes neuroinflammation. This study aimed to determine whether binge EtOH exposure (intragastric 3 g/kg 25% EtOH every 8 hours for 4 days) would induce the expression of cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
30
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 59 publications
12
30
1
Order By: Relevance
“…1, EtOH alone failed to induce C6 cells to secrete this cytokine. This is consistent with Zahr et al (2010), who described that binge EtOH treatment for 4 days was insufficient to induce the expression of several cytokines, including TNFα in blood, liver, or different brain regions of rats. In addition, our results showed that co-incubation of C6 cells with EtOH plus LPS abrogated LPS-induced TNFα release in these cells.…”
Section: Resultssupporting
confidence: 93%
“…1, EtOH alone failed to induce C6 cells to secrete this cytokine. This is consistent with Zahr et al (2010), who described that binge EtOH treatment for 4 days was insufficient to induce the expression of several cytokines, including TNFα in blood, liver, or different brain regions of rats. In addition, our results showed that co-incubation of C6 cells with EtOH plus LPS abrogated LPS-induced TNFα release in these cells.…”
Section: Resultssupporting
confidence: 93%
“…Age of the alcohol exposure might play an important role in cytokine response, as previous studies of alcohol exposure in adolescent and adult rats found no change in TNF-α expression (Marshall et al, 2013; McClain et al, 2011; Zahr et al, 2010), while this cytokine was upregulated in the neonatal rodent cerebral cortex, hippocampus, and cerebellum (Drew et al, 2015; Topper et al, 2015). IL-1β gene expression was also increased in all three brain regions in the study from Drew and colleagues (20150), while upregulation was only present in the cerebellum in the report by Topper et al, 2015, possibly due to differences in the exposure paradigm and time points used.…”
Section: Discussionmentioning
confidence: 94%
“…The effects of ethanol on the CNS are complex and appear to vary depending on the peak blood ethanol concentration, treatment paradigm (including length of treatment and the presence or absence of a withdrawal period following ethanol administration), and the age of the animal (reviewed in Drew and Kane, 2013). A short term 4-day binge ethanol treatment did not result in CNS inflammation in rats, for example (Zahr et al, 2010a). In contrast, and although it varied from study to study, long-term acute or chronic ethanol exposure resulted in glial activation and production of inflammatory molecules such as nitric oxide, cyclooxygenase-2, cytokines including TNF-α and IL-1β, and chemokines including CCL2, MIP-1α/CCL3, and MIP-1β/CCL4 (Alfonso-Loeches et al, 2010; He and Crews, 2008; Pascual et al, 2009; Qin et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…The effects of ethanol on immune activation in the adult brain have been more extensively studied and the results vary significantly, likely due to differences in the experimental paradigms employed. For example, a short term acute model of ethanol exposure did not result in production of immune molecules in the adult CNS (Zahr et al, 2010a), while longer term acute or chronic ethanol exposure resulted in the CNS production of pro-inflammatory molecules (Alfonso-Loeches et al, 2010; Pascual et al, 2009; Qin et al, 2008). Interestingly, our studies demonstrating an absence of CCL2 induction by ethanol in the adolescent brain may contribute to increased vulnerability of the adolescent CNS to ethanol neuropathology, behavioral dysfunction, and risk of addiction as CCL2 has been shown to be protective against ethanol effects in some models (Bray et al, 2013).…”
Section: Discussionmentioning
confidence: 99%